Blackberry and Dewberry: Biology and Control - Brent Sellers; Pratap Devkota; Jason Ferrell (EDIS)
Blackberry and dewberry are often viewed simply as nuisance weeds that reduce grazing in a portion of the field. This may not seem that detrimental. However, severe financial losses can occur if cattle are injured by these growing thickets. For example, a bull's reproductive organs can be severely damaged by blackberry or dewberry thorns. Lesions or scratches from the thorns may result in infection or complete loss of reproductive performance. Lactating cows and dairy cows are not safe either. Thorns can scratch and cause infections of the udder, which may result in lower milk production. Therefore, blackberry infestations can result in monetary losses from both reduced grazing and potential animal injury. https://edis.ifas.ufl.edu/ag238